Intellectual capital, CSR, and earnings quality impact on equity cost of capital - Fivi Anggraini; Ethika Ethika; Selvi Adenia Safitri (Journal of Business & Banking, 2024)
Companies need additional funds to improve their business activities, and one source of these funds is investors, which involves the cost of equity capital. Several factors influence the cost of equity capital, including the disclosure of intellectual capital, corporate social responsibility (CSR), and earnings quality. This study empirically examines the impact of intellectual capital disclosure, CSR, and earnings quality on the cost of equity capital. The research sample consists of 30 manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange during the 2017-2021 period. The results show that intellectual capital disclosure, CSR, and earnings quality significantly affect the cost of equity capital in manufacturing companies within the consumer goods industry. Higher disclosures of intellectual capital and CSR are expected to enhance a company’s transparency and reputation, thereby reducing the cost of equity capital. However, the findings also indicate that increased disclosure can heighten investors’ perceived risk, which, in turn, raises the cost of equity capital. The implication is that companies need to balance information disclosure to effectively manage perceived risk and optimize the cost of equity capital.